2 enhanced 2 x 2 y 3 x 2 3 xy 3 y 2 2 xy x3 y 3 1 2

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 2 y L.C.M. 3 x + x − 14 = ( x − 2)(3x + 7) 2 = 23 × 3 × ( x + 2 y) × ( x − 2 y) 2 × ( x + 3 y) = 24( x + 2 y )( x − 2 y ) 2 ( x + 3 y ) 9 x 2 + 21x = 3 x(3 x + 7) ∴ H.C.F. = 3 x + 7 9. (a) (i) ∵ L.C.M. = 3 x( x − 2)(3 x + 7) f (1) = 2(1)3 − 5(1) 2 − 17(1) + 20 = 2 − 5 − 17 + 20 =0 ∴ By the factor theorem, x – 1 is a factor of 5. f(x). 9 x 2 − 12 x + 4 = (3 x − 2) 2 (ii) By long division, we have 18 x 2 − 8 = 2(9 x 2 − 4) = 2[(3 x) 2 − 2 2 ] = 2(3 x + 2)(3 x − 2) ∴ ∴ H.C.F. = 3 x − 2 (b) 2 L.C.M. = 2(3 x + 2)(3x − 2) 6. f ( x ) = ( x − 1)(2 x 2 − 3 x − 20) f ( x ) = ( x − 1)( x − 4)(2 x + 5) g ( x) = 2 x 2 + 11x + 15 = ( x + 3)(2 x + 5) ∴ − 6 + 24 x 2 = 6 × (4 x 2 − 1) = 6 × [(2 x) 2 − 1] = 2 × 3 × (2 x + 1) × (2 x − 1) H.C.F. L.C.M. 8 x 2 − 20 x − 12 = 4 × ( 2 x 2 − 5 x − 3) = 2 2 × (2 x + 1) × ( x − 3) 13 = 2x + 5 = ( x − 1) × ( x + 3) × ( x − 4) × (2 x + 5) = ( x − 1)( x + 3)( x − 4)(2 x + 5) NSS Mathematics in Action Worksheets 4B 8 More about Polynomials (II) Worksheet 8.2 (Enhanced) 2 x − 2 y 3 x 2 + 3 xy + 3 y 2 × 2 xy x3 − y 3 1. 2( x − y ) 3( x 2 + xy + y 2 ) × 2 2 2 xy ( x − y )( x + xy + y ) 3 = xy = 5. x 3x 5x + + (5 x − 1)(3 x − 2) (3x − 2)( x + 3) (1 − 5 x)( x + 3) x( x + 3) 3x(5 x − 1) = + (5 x − 1)(3 x − 2)( x + 3) (5 x − 1)(3x − 2)( x + 3) 5 x (3 x − 2) − (5 x − 1)(3x − 2)( x + 3) = x 2 + 3x + 15 x 2 − 3x − 15 x 2 + 10 x (5 x − 1)(3x − 2)( x + 3) x 2 + 10 x (5 x − 1)(3 x − 2)( x + 3) x( x + 10) = (5 x − 1)(3 x − 2)( x + 3) = 2. 4x x2 − y2 −2 9 x − 6 y 3x − 5 xy + 2 y 2 4x ( x + y )( x − y ) = − 3(3 x − 2 y ) (3 x − 2 y )( x − y ) 4x x+ y = − 3(3 x − 2 y ) 3 x − 2 y 4 x − 3( x + y ) = 3(3 x − 2 y ) x − 3y = 3(3 x − 2 y ) x −1 8x3 + 1 1 + 4x + 4x 2 ×2 ÷ 4x − 2x + 1 x −1 x2 + x x −1 (2 x) 3 + 1 (1 + 2 x ) 2 =2 × ÷ 4 x − 2 x + 1 ( x + 1)( x − 1) x( x + 1) 2 3 1 + − 2 x 2 − 7 x − 15 x 2 − 3 x − 10 2 x 2 + 7 x + 6 2 3 1 = + − ( x − 5)(2 x + 3) ( x − 5)( x...
View Full Document

This document was uploaded on 03/03/2014.

Ask a homework question - tutors are online